دور إدارة المعرفة في عدم التأكد عند إتخاذ القرار: دراسة حالة : شركة سكر كنانة المحدودة - 2019 م - د السماني محمد الغالي نور الدائم (White Nile Journal for Studies and Research, 2019)
This research has discussed the problem in a main question about thecontributionof acknowledgement administrationin reducing uncertainty risks related to decision making, and the relation between acknowledgment administration and decision making process, does acknowledgment administration effects in reducing uncertainty risks. The research aims to recognize acknowledgment concepts and operations, studying acknowledgement administration effect on reducing uncertainty risks related to decision making. From the research hypothesis, there is a statistical relation between acknowledgment administration and decision making. acknowledgementadministrationeffectsonreducing uncertainty risks related to decision making, decision making efficiency related to acknowledgment administration efficiency. The researcher has used the descriptive method to layout the theoretical framework and study case, the deductive method to device the problem and general framework for the research, statistical analytical method for analyzing data and hypothesis testing. From the research findings, there is a relationship between knowledge and decision making, decision making efficiency depends on acknowledgment administration efficiency, giving more attentiontoall kind of knowledge while making decisions.. The recommendation are, the necessity linking decision making with knowledge, increasing acknowledgment administration efficiency to assure decision making efficiency, giving more attention to all kind of knowledge through making decisions.